Alanine Mutagenesis in the Complementarity Determining Region 3 of the MTB and HIV-1 Peptide-Bispecific T Cell Receptor Beta Chain Affects Ligand Recognition - Zhou, Chao-Ying; Wang, Rui-Ning; Wen, Qian; He, Wen-Ting; Zhang, Shi-Meng; Du, Xia-Lin; Yang, Jia-Hui; Ma, Li (Frontiers in Immunology, 2017)
Mycobacterium tuberculosis/human immunodeficiency virus (MTB/HIV) coinfection presents a special challenge to the prevention and treatment of tuberculosis and HIV/AIDS. Adoptive transfer of high-affinity T cell receptor (TCR) gene-modified T cells against MTB and HIV antigens is a promising approach to treating MTB/HIV coinfected patients whose cellular immunity is obviously disordered. We have previously successfully identified that a bispecific TCR screened out from peripheral blood mononuclear cells of a HLA-A*0201+ healthy individual using the complementarity determining region 3 (CDR3) spectratype analysis recognizes both MTB Ag85B199-207 and HIV-1 Env120-128 peptide. However, it has not been known how residues on CDR3 loops which have been shown to play a leading role in antigen binding and specificity contribute to the bispecific TCR contact with the peptide-major histocompatibility complex (MHC) complexes. In this study, we provided an extensive investigation of residues in the predicted CDR3 of the bispecific TCR beta (β) chain using alanine scanning mutagenesis. Our data showed that three of the five substituted residues (G115A, T116A, A117G) in CDR3β of the bispecific TCR caused a significantly diminished T cell response to antigen, whereas the remaining two substituted residues (D114A, S118A) resulted in completely eliminated response, thus identifying the two residues that were particularly critical for the recognition of peptide-MHC in the bispecific TCR. These findings will provide an imperative foundation for generating an improved high-affinity bispecific TCR for use in T cell adoptive immunotherapy for MTB/HIV coinfected individuals.